Evolutionary Biology and Drug Development - Rehan Haider (International Journal of Integrative Sciences, 2023)
Evolution is the unifying framework in biology and scales to all dwelling systems. It is the central organizing questioning to grant clarification for reputedly disparate herbal phenomena; from the very small (individual molecules) to the very large (ecosystems), from the upward push and unfold of molecular editions to the habits and physique shapes of elephants. In modern times, our maintain shut for evolution in medicinal pills has acquired momentum. Individuals have championed the cause, dedicated journals have emerged, and new books on the trouble are often posted (“The Evolution and Medicine Review” is an terrific web-based advisable useful resource presenting up to date information on the subject, http://evmedreview.com). This union between evolution and cure has already most fulfilled our hold close of pathological techniques (Maccallum, 2007, Nesse & Stearns, 2008). Drug enchancment and therapeutic strategies are areas in which evolutionary standards would perchance moreover be specially helpful. The avalanche of bioinformatic methods, genomic data, and the subsequent emergence of evolutionary genomics in the ultimate few many years propose that integrating these fields into drug graphs is now a possibility. Incorporating evolutionary documents is now not completely really useful a posteriori when we might also moreover in addition hope to apprehend why resistance to a special compound emerged. It is in addition treasured a priori, to structure increased efficacious drugs, suggest possible resistance profiles and conceptualize novel therapeutic strategies